2012
DOI: 10.1097/scs.0b013e31824de328
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Complications Following Endoscopically Assisted Treatment of Mandibular Condylar Fractures

Abstract: Although we cannot draw statistically significant conclusions, we think that further randomized clinical trials should be necessary to analyze this method; we believe that there is not an ideal approach for a fracture, but each patient needs to be fully evaluated carefully preoperatively, and the more convenient approach needs to be selected for each case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…Other alternatives to decrease the incidence of FN damage with the retromandibular approach are intraoral endoscope-assisted fixation (Arcuri et al, 2012), anteroparotid transmasseteric approach (Wilson et al, 2005), mini retromandibular transparotid approach (Biglioli and Colletti, 2008), submandibular approach and the transoral approach (Pereira-Filho et al, 2011). Intraoral endoscope-assisted fixation suffers from disadvantages such as limited access, particularly in medially displaced/dislocated fractures, need for expensive equipment, increased operative time, a steep learning curve and a FN damage incidence similar to extraoral methods of fixation of the condyle (Haug and Brandt., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Other alternatives to decrease the incidence of FN damage with the retromandibular approach are intraoral endoscope-assisted fixation (Arcuri et al, 2012), anteroparotid transmasseteric approach (Wilson et al, 2005), mini retromandibular transparotid approach (Biglioli and Colletti, 2008), submandibular approach and the transoral approach (Pereira-Filho et al, 2011). Intraoral endoscope-assisted fixation suffers from disadvantages such as limited access, particularly in medially displaced/dislocated fractures, need for expensive equipment, increased operative time, a steep learning curve and a FN damage incidence similar to extraoral methods of fixation of the condyle (Haug and Brandt., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Arcuri et al [19] based on their data records from 14 patients who underwent surgical repair of subcondylar fractures by transoral endoscopic-assisted technique showed 4 complications experienced by 4 different patients: (1) arterial hemorrhage, (2) facial nerve injury, (3) nonunion, (4) partial condylar reabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…Most surgeons have preferred the use of endoscopes (Gonzalez-Garcia et al, 2009;Kellman et al, 2009;Schmelzeisen et al, 2009;Kang et al, 2012;Kokemueller et al, 2012), and some of them consider endoscopy as absolutely essential (Sharif et al, 2010;Neff, 2011 (Arcuri et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile several authors have since reported their experiences, but only as early experiences and in small case numbers (Kanno et al, 2011;Arcuri et al, 2012;Schiel et al, 2013).…”
Section: Introductionmentioning
confidence: 97%